Development Ecosystem E-Booklet in Karimunjawa National Park as a Supplement to Teaching Materials to Improve Learning Outcomes of SMA N 1 Donorojo Students - Erisca Candra Setyana; Sri Ngabekti (Journal of Biology Education, 2024)
Karimunjawa National Park is a conservation area in the northern part of the Java Seawhich has 5 types of ecosystem. This research aims to conduct research for materials for developing ecosystem e-booklets in Karimunjawa National Park as a supplement to teaching materials and test the validity, readability and effectiveness of e-booklets to improve student learning outcomes. This research is a type of research and development or R&D (research and development). The development procedure used in developing this e-booklet is the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). The biological research method used is pure descriptive research or survey by conducting explorationField data collection in Karimunjawa National Park, Designe-bookletwhich has been valid after being revised based on validator input and high readability, then tested for effectiveness. Testing the effectiveness of the e-booklet was carried out on cognitive, affective and psychomotor aspects using post-test question instruments, attitude assessment questionnaires and LKPD. The effectiveness test was carried out on 33 class X students. The results of the research showed that the ecosystem in Karimunjawa National Park was in good condition with diverse flora and fauna. The ecosystem e-booklet in Karimunjawa National Park is very suitable, has high readability, and is effective for improving learning outcomes in cognitive, affective and psychomotor aspects. Based on the research results, it can be concluded that the ecosystem e-booklet in Karimunjawa National Park as a supplement to teaching materials is effective in improving the learning outcomes of students at SMA Negeri 1 Donorojo.